Keterlibatan Peran Orang Tua Dalam Pelaksanaan Blended Learning Pada Masa Pandemi Di Desa Enggal Rejo Kabupaten Pringsewu - Sri Ilham Nasution; Ika Mislaili Yana (Jayapangus Press, 2022)
This research describes the involvement of the role of parents in the implementation of blended learning during the covid-19 pandemic in Enggal Rejo village of Pringsewu Regency. The method in this study is qualitative with parent informants and children aged 6 to 12 years, data collection techniques using observation, interviews, and documentation. The results showed that the involvement of parents in the implementation of blended learning during the pandemic acted as facilitators, motivators, as teachers and as influences. In addition, the difficulties faced by parents include; Low educational background, weak economy, parental employment and limited time.